Influence of the MgO-TiO2co-additive content on the phase formation, microstructure and fracture toughness of MgO-TiO2-reinforced dental porcelain nanocomposites - Ranida Waiwong (2018)
The influence of the co-additive concentration (0 - 45 wt% with an interval of 5 wt%) of MgO-TiO 2 on the phase formation, microstructure and fracture toughness of MgO-TiO 2 -reinforced dental porcelain nanocomposites derived from a one-step sintering technique were examined using a combination of X-ray diffraction, scanning electron microscopy and Vickers indentation. It was found that MgO-TiO 2 -reinforced dental porcelain nanocomposites exhibited significantly higher fracture toughness values than those observed in single-additive (MgO-TiO 2 )-reinforced dental porcelain composites at any given sintering temperature. The amount of MgO-TiO 2 as a co-additive was found to be one of the key factors controlling the phase formation, microstructure and fracture toughness of these nanocomposites. It is likely that 30 wt% of MgO-TiO 2 as a co-additive is the optimal amount for MgO-TiO 2 5 and MgO-TiO 2 4 crystalline phase formation to obtain the maximum relative density (96.80%) and fracture toughness (2.60 ± 0.07 MPa·m1/2) at a sintering temperature of 1000°C.